Optimalisasi Pelaporan Saldo Kas di Bendahara Pengeluaran oleh Kantor Pelayanan Perbendaharaan Negara (KPPN) Jakarta II dengan Pendekatan Soft System - Ria Dewi Ambarwati (Jurnal Riset Akuntansi Terpadu, 2020)
This research discusses the optimization of cash balance report in Disbursing Treasurer by KPPN Jakarta II. This study is a qualitative research with soft system methodology approach. The objective of this study is to identify the problems faced by KPPN Jakarta II in reporting cash balance in Disbursing Treasurer and to formulate recommendations to solve the problems. This research shows some problems such as noncompliance, lack of coordination, ineffective sanctions, and emergence of idle cash. Several recommendations resulted from this research are to conduct assessment for work unit performance, to enhance employee’s competence, to establish internal reconciliation team and monitoring system of cash balance in Disbursing Treasurer.